A review of turbulence measurement techniques for flotation. (September 2016) - Meng, Jun; Tabosa, Erico; Xie, Weiguo; Runge, Kym; Bradshaw, Dee; Manlapig, Emmanuel
Highlights: Turbulence as an important factor to flotation has been reviewed. Techniques measuring fluid flows have been reviewed according to their categories. The strengths and weakness of each technique has been analysed. Suitable techniques for three phase flow turbulence measurements were identified. Abstract: Flotation is one of the most important primary separation processes in the minerals industry. As far as the mechanism of flotation is concerned, turbulence is one of the key parameters determining flotation performance because it affects three main processes: suspension of particles, air dispersion and particle-bubble collision, attachment and detachment. To study turbulence in industrial flotation cells, both numerical simulation and experimental measurement can be performed. Development of turbulence models and validation of Computational Fluid Dynamic (CFD) numerical simulation need experimental data obtained from turbulence measurement techniques that can be used in the three phase abrasive opaque environment present in a flotation cell. In this paper, the different techniques which have been used to characterise turbulence in the literature are reviewed in terms of their basic principles, system structure, range of application and limitations. Laser Doppler Anemometry (LDA), Particle Image Velocimetry (PIV), Constant Temperature Anemometer (CTA) and the Aeroprobe are all techniques that have been widely used to characterise the turbulence created in flotation machines operating with only fluid (or fluid and air). They cannot however be used when the concentration of solids is high as commonly occurs in a flotation machine. Techniques that have been identified that have the potential to be used to produce accurate measurements in three phase flows include Positron Emission Particle Tracking (PEPT), Piezoelectric Vibration Sensor (PVS) and Electrical Resistance Tomography (ERT). It is envisaged that applications of PEPT in three phase flotation cells will mostly be confined to studies at the laboratory scale. ERT has been tested in flotation cells filled with water and air but needs more development before it can be applied confidently in industrial scale flotation units. PVS, on the other hand, has been validated at laboratory scale and has been applied successfully for measuring turbulence in large scale operating flotation machines.